2017
DOI: 10.1002/jcp.25693
|View full text |Cite
|
Sign up to set email alerts
|

Homocysteine as a Pathological Biomarker for Bone Disease

Abstract: In the last few decades, perturbation in methyl-group and homocysteine (Hcy) balance have emerged as independent risk factors in a number of pathological conditions including neurodegenerative disease, cardiovascular dysfunction, cancer development, autoimmune disease, and kidney disease. Recent studies report Hcy to be a newly recognized risk factor for osteoporosis. Elevated Hcy levels are known to modulate osteoclastgenesis by causing detrimental effects on bone via oxidative stress induced metalloproteinas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
50
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(58 citation statements)
references
References 75 publications
0
50
0
1
Order By: Relevance
“…Low bone mineral density (BMD) is a common geriatric problem, and it has been hypothesized that the metabolism of HCy is involved in osteoporosis, increasing the risk of osteoporotic fracture [1]. In the Framingham study [173] on 825 men and 1174 women aged from 59 to 91 years, with a follow up 12.3 years for men and 15.0 years for women, it was observed that HHcy (>20 µmol/L for men and >18 µmol/L for women) is associated with higher risk of bone fracture, almost 4 times as high for men and 1.9 times as high for women.…”
Section: Osteoporosismentioning
confidence: 99%
See 1 more Smart Citation
“…Low bone mineral density (BMD) is a common geriatric problem, and it has been hypothesized that the metabolism of HCy is involved in osteoporosis, increasing the risk of osteoporotic fracture [1]. In the Framingham study [173] on 825 men and 1174 women aged from 59 to 91 years, with a follow up 12.3 years for men and 15.0 years for women, it was observed that HHcy (>20 µmol/L for men and >18 µmol/L for women) is associated with higher risk of bone fracture, almost 4 times as high for men and 1.9 times as high for women.…”
Section: Osteoporosismentioning
confidence: 99%
“…Homocysteine (Hcy) is a significant biomarker for overall health status and, although it is not clear whether the Hcy represents an indicator rather the etiology of disease, a direct relationship between its elevated fasting plasma levels and several pathological disorders, including bone health [1], neurodegenerative disease, [2], renal dysfunction [3], cognitive impairments [4], and congenital defect development [5], as well as its status of independent risk factor in coronary heart and cerebrovascular disease, is widely supported by scientific literature [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Latest research regarding bone fraglility try to identify the mechanism that lead to osteoporosis. Some studies indicate the mechanism of reactive oxygen species as a possible cause of bone fragility [19][20][21][22], other consider homocysteine as a possible cause for the disease [23][24][25][26]. Many literature data show that homocysteine levels are directly linked to oxidative mechanims and both may be involved in bone remodeling [27,28,29,30].…”
Section: Resultsmentioning
confidence: 99%
“…Elevated serum levels of homocysteine have deleterious effects on vascular endothelial cells, bone, neural cells [11]. Recent studies indicate that homocysteine is involved in bone matrix degradation and altered biomechanical bone properties through osteoclasts activity [12]. A possible mechanism by which homocysteine is involved in bone metabolism is the destruction of the cross-linking of collagen molecules and the increase in the level of advanced endoglicant products.…”
mentioning
confidence: 99%